Respiratory morbidity in very low birth weight infants through childhood and adolescence. Issue 6 (3rd March 2021) - Littner, Yoav; Volinsky, Chen; Kuint, Jacob; Yekutiel, Naama; Borenstein‐Levin, Liron; Dinur, Gil; Hochwald, Ori; Kugelman, Amir
Abstract: Objective: To describe the long‐term (up to 18 years of age) respiratory outcomes of children and adolescents born at very low birth weight (VLBW; ≤1500 g) in comparison with that of children born >1500 g. Methods: An observational, longitudinal, retrospective study comparing VLBW infants with matched controls, registered at a large health maintenance organization in Israel. Pulmonary outcomes collected anonymously from the electronic medical files included respiratory illness diagnoses, purchased medications for respiratory problems, office visits with either a pediatric pulmonologist or cardiologist and composite respiratory morbidity combining all these parameters. Results: Our study included 5793 VLBW infants and 11, 590 matched controls born between 1998 and 2012. The majority (99%) of VLBW infants were premature (born < 37 weeks' gestation), while 93% of controls were born at term. The composite respiratory morbidity was significantly higher in VLBW infants compared with controls in all age groups (relative risk [95% confidence interval]: 1 year: 1.22 [1.19–1.26], <2 years: 1.30 [1.27–1.34], 2–6 years: 1.29 [1.27–1.32], 6–12 years: 1.53 [1.47–1.59], 12–18 years: 1.46 [1.35–1.56]; respectively). Both VLBW infants and controls demonstrated a steady decline in the composite respiratory morbidity with aging. In VLBW infants, lower gestational age was associated with higher respiratory morbidity only until 2 years of age and the morbidity declined in each gestational age group until adolescence. Conclusion: Our study confirmed a strong association between VLBW and pulmonary morbidity. The higher prevalence of respiratory composite morbidity in VLBW infants persists over the years until adolescence. The respiratory morbidity is most evident in the first year of life and declines afterward.